Quasi-static indentation behaviour of glass fibre reinforced polymer - Ayob, Amran (Trans Tech Publications, 2014)
Fibre reinforced polymer (FRP) plates subject to quasi-static indentation loading were studied. The plates were fabricated from three layers of chopped strand mat glass fibre and polyester resin using vacuum infusion process. Indentation tests were conducted on the plates with loading rates of 1 mm/min, 10 mm/min, 100 mm/min and 500 mm/min using a hemispherical tip indenter with diameter 12.5 mm. The plates were clamped in a square fixture with an unsupported space of 100 mm 100 mm. The loads and deflections at the indented location were measured to give energy absorption-deflection curves. The results showed that the loading rate has a large effect on the indentation behaviour and energy absorbed.